The study of slurry recirculation to increase biogas productivity from Jatropha curcas Linn. capsule husk in two phase digestion - Hendroko S, Roy; Sasmito, Andi; G Adinurani, Praptiningsih; Nindita, Anggi; Yudhanto, Agus Setyo; Adhi Nugroho, Yogo; Liwang, Tony; Mel, Maizirwan (Elsevier, 2015)
The purpose of this study was to obtain the best slurry recirculation treatment for two-phase digester system which produced the highest biogas production in the DH-JcL substrate. The study was conducted in the laboratory using 750 mL and 2 L of plasticdigester and biofilter plastic as growth immobilize. The slurry recirculation treatment consisted of the recirculation of 50 %slurry to methanogenesis digester, 50 % slurry to hydrolysis digester, and 25 % slurry to hydrolysis digester combined with 25 % to methanogenesis digester. The highest daily biogas production was obtained from the recirculation of 50 % slurry to hydrolysis digester. However, the best slurry recirculation treatment, which was more stable in longer period, was 50 % slurry to methanogenesis digester.